Controllable synthesis of ultra-long YCexOy:Eu3+ nanowire arrays and fluorescence activation of Ce3+. (August 2018) - Feng, Jie; Wang, Qian; Li, Peng; Ye, Lina; Xiang, Ji; Peng, Guangzheng; Du, Yuanxin; Zhu, Manzhou; Yuan, Xiaoyou
Graphical abstract: Highlights: Ultra-long YCex Oy :Eu 3+ nanowire arrays is realized by controllable synthesis. Ce 3+ ion dominates the fluorescence activation in YCex Oy :Eu 3+ nanowire arrays. Fluorescence emission in red light area is useful in medical image or cell labeling. Abstract: Ultra-long YCex Oy :Eu 3+ nanowire arrays(NWAs) have been synthesized in anodic aluminum oxide (AAO) templates by chemical co-deposition at negative pressure suction, which are amorphous, and possess precise dimension and homogeneous morphologies. The SEM, TEM, XRD and EDS were employed to investigate the morphology, structure and elemental composition of YCex Oy :Eu 3+ NWAs. The fluorescence properties of the YCex Oy :Eu 3+ NWAs were measured by fluorescence spectrometer (PerkinElmer LS-55) using Xenon discharge lamp as the excitation light source. There are two emission peaks at 615 nm and 702 nm with excitation wavelength of 394 nm, which corresponds to the 5 D0 - 2 F2 and 5 D0 - 7 F4 energy level transition of Eu 3+, respectively. The fluorescence intensity of YCex Oy :Eu 3+ NWAs is related to the doping concentration of Eu 3+ ion, which reaches a maximum with doping concentration of Eu 3+ at 8%, and remarkably decreases at higher concentrations. Ce 3+ ion dominates the fluorescence activation in YCex Oy :Eu 3+ NWAs.